Pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Campaigners fighting against the use of hazardous pesticides maintain that very little is done to inform local users in the Third World about the dangers of these chemicals. The Pesticide Action Network (PAN) says that most of the pesticides...